Proceedings of the International Conference on Teacher Training and Education 2018 (ICTTE 2018) 2018
DOI: 10.2991/ictte-18.2018.11
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Environmental Education at the Adiwiyata Program Recipient School in Growing Ecoliteracy of Students

Abstract: This research is a descriptive and explorative research that aims to find out how the integration of environmental education in Adiwiyata recipient schools in growing the students' ecoliteracy through intracurricular and extracurricular program. This research uses qualitative approach with case study method conducted in one of public elementary school which has received Adiwiyata award 2018. Technique of collecting data using interview, observation, and curriculum document study. The data has been collected an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 5 publications
1
4
0
2
Order By: Relevance
“…Based on the eco-literacy evaluation test results, it was found that the students' cognitive ecoliteracy abilities could be categorized as good. It corroborates with the research by Adela, Sukarno & Indriayu (2018), which stated that the ability to understand elementary school students' eco-literacy, especially schools that implemented the Adiwiyata program, could be categorized as very good. Adiwiyata program itself is an environmental education program.…”
Section: Cognitive Aspectsupporting
confidence: 89%
“…Based on the eco-literacy evaluation test results, it was found that the students' cognitive ecoliteracy abilities could be categorized as good. It corroborates with the research by Adela, Sukarno & Indriayu (2018), which stated that the ability to understand elementary school students' eco-literacy, especially schools that implemented the Adiwiyata program, could be categorized as very good. Adiwiyata program itself is an environmental education program.…”
Section: Cognitive Aspectsupporting
confidence: 89%
“…Los criterios emitidos por los especialistas presentes en el taller sobre los resultados del diagnóstico coinciden en que el estudio fue amplio y diverso; plantearon además que, fundamentar el modelo pedagógico desde la pedagogía crítica y el constructivismo social, hace que la tesis sea consecuente con los sustentos pedagógicos del proceso educativo en el país. Hubo consenso en la importancia de esta experiencia y la necesidad de desarrollar otras para trabajar la formación ambiental de los futuros profesionales, lo que se corrobora en otras investigaciones como la realizada por (Adela et al, 2018). Los participantes sugirieron considerar las habilidades o competencias para el desarrollo de los procedimientos (saber hacer); resaltaron la necesidad de trabajar las actitudes y comportamientos de los jóvenes e involucrarles en la autoevaluación de sí mismos, para alcanzar las competencias para la sostenibilidad, cuestiones que coinciden con las planteadas por (Sengupta et al, 2020) en su obra que trata sobre las estrategias de enseñanza y aprendizaje para el desarrollo sostenible.…”
Section: Tercera Fase De La Investigaciónunclassified
“…This ritual is carried out to be able to live side by side with the universe and respect and maintain the presence of nature. Empathy for all forms of life can be developed by integrating environmental education into everyday life [18]. The Tuk Babon tradition is carried out by accompanying mountains of produce around the village before being taken to a spring which is located 1.5 km from the residential area.…”
Section: Implementation Of Patri Tuk Babonmentioning
confidence: 99%